2016
DOI: 10.1103/physrevb.94.035163
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle lifetime broadening in resonant x-ray scattering ofNH4NO3

Abstract: It has been previously shown that two effects cause dramatic changes in the x-ray absorption and emission spectra from the N K edge of the insulating crystal ammonium nitrate. First, vibrational disorder causes major changes in the absorption spectrum, originating not only from the thermal population of phonons, but, significantly, from zero-point motion as well. Second, the anomalously large broadening (~ 4 eV) of the emission originating from nitrate σ states is due to unusually short lifetimes of quasiparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 50 publications
(64 reference statements)
1
42
0
Order By: Relevance
“…Each structure in the ensemble is a possible configuration of a subset of the atoms within the crystal. To generate the ensemble of disordered structures we make use of the phonon-mode approach introduced previously [2,3], and expanded on in [13] and separately in [14]. Briefly, the phonon modes of a structure are assumed to be harmonic.…”
Section: A Phonon Bandstructure and Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Each structure in the ensemble is a possible configuration of a subset of the atoms within the crystal. To generate the ensemble of disordered structures we make use of the phonon-mode approach introduced previously [2,3], and expanded on in [13] and separately in [14]. Briefly, the phonon modes of a structure are assumed to be harmonic.…”
Section: A Phonon Bandstructure and Disordermentioning
confidence: 99%
“…An additional, Gaussian broadening of 0.25 eV (0.50 eV) was applied to the calculated absorption (emission) spectra before averaging. The alignment of the XAS energy scale of the ocean calculations follows previous work [3]. The emission energy of the calculations is fixed relative to the absorption alignment, including the band-gap correction from the GW.…”
Section: B Calculationsmentioning
confidence: 99%
“…This effect can be modeled by summing calculated absorption and RIXS spectra over a representative ensemble of structures. Previously it was shown that such structures can be generated by considering the phonon modes of the system within a harmonic approximation [27, 28], and this technique has since been independently adopted elsewhere [29]. The advantage of the phononmode approach is that the quantum nature of the nuclear wave functions, i.e., zero-point motion, is included automatically, whereas in standard molecular dynamics simulations the nuclei are classical particles.…”
Section: Ground-state Propertiesmentioning
confidence: 99%
“…The energy scale of the spectrometer was calibrated using elastic scattering of the excitation radiation. The details of the monochromator and spectrometer energy calibration have been previously described [28]. …”
Section: X-ray Spectramentioning
confidence: 99%
See 1 more Smart Citation